Centralization can jeopardize local wild plant-based food security. Issue 1 (31st December 2023) - Mattalia, G; Prakofjewa, J; Kalle, R; Prūse, B; Marozzi, M; Stryamets, N; Kuznetsova, N; Belichenko, O; Aziz, M.A; Pieroni, A; Sõukand, R
ABSTRACT: Centralization is one mechanism of authoritative control, where citizens receive operation guidelines from a single source. This can impact various spheres of life including local gastronomic knowledge, a cornerstone of biocultural diversity. We explored how to evaluate the effects of Soviet centralization on wild food plant local gastronomic knowledge. We considered four case studies of ethnic communities that are divided by political borders. In total, we conducted 581 semi-structured interviews. Our results suggest three main findings. The first regards the high similarity of use of wild food plants among the communities living in Russia and Finland. The second involves the higher proportion of simple preparations made with wild food plants in Soviet contexts, which is not evident in adjacent non-Soviet countries. The third concerns the low(er) number of distinct wild plant-based foods retained by non-Soviet countries and, in post-Soviet contexts, those that refer to past uses. We argue that the erosion of wild food plant-based local gastronomic knowledge guided by homogenization and repression poses a serious risk to local food security.